ANALISIS PREDIKSI FINANCIAL DISTRESS MENGGUNAKAN MODEL ALTMAN Z-SCORE PADA PERUSAHAAN RITEL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Nur Khasanah, Melinda; Rosmini Ramli (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
The objective of this study is to examine the forecast of financial difficulties employing the Altman Z-Score model among retail firms that are publicly traded on the Indonesia Stock Transactions between 2018 and 2022 were examined in this research, which utilized a quantitative methodology with a descriptive approach. The study involved a total of 33 companies, with a sample of 9 companies selected using purposive sampling. The findings indicated that 8 retail companies were identified to be potentially facing distress conditions. These companies include CARS and HERO during the period of 2020-2022, MKNT in 2022, TELE from 2019-2022, as well as GLOB, IMAS, MPPA, and TRIO, which exhibit a potential for financial distress over a span of five consecutive years.